Permafrost thaw challenges and life in Svalbard - Ulla Timlin; Alexandra Meyer; Tanja Nordström; Arja Rautio (Current Research in Environmental Sustainability, 2022)
Svalbard is facing changes related to climate change and permafrost thaw, which have impacts on the life and well-being of people. This study evaluated impacts of climate change and permafrost thaw on the life of locals living in Longyearbyen, Svalbard and focused on investigating self-rated health, well-being, quality of life, satisfaction with life, and feeling of empowerment when facing the changes and impacts. The aim was to find out which perceived environmental and adaptation factors relate to these dependent variables. The data was collected using a multidisciplinary questionnaire (n = 84); for statistical analysis cross-tabulation was used and the associations were tested either by the Pearson χ2 test or Fisher's exact test, when appropriate. Binary logistic regression analysis was used to investigate associations between the dependent variables and perceived environmental and adaptation factors. Results suggested that well-being, quality of life, satisfaction with life, and life balance (a sum variable of earlier parameters) were associated with the recognized challenges related to infrastructure or physical environment. Quality of life and life balance were supported by the opinion that not enough has been done to adapt to permafrost thaw by national and global authorities. Despite recognized challenges, participants appear to live satisfied lives. People seemed to have knowledge about the impacts of permafrost thaw, they wanted to adapt to the changes, but more actions are needed from national and global authorities. Research with a larger sample size is needed due to the complexity of the relationships between people, holistic well-being, and climate change.